The first solid-state route to luminescent Au(I)—glutathionate and its pH-controlled transformation into ultrasmall oligomeric Au10–12(SG)10–12 nanoclusters for application in cancer radiotheraphy - Deák, Andrea; Szabó, Pál T.; Bednaříková, Vendula; Cihlář, Jaroslav; Demeter, Attila; Remešová, Michaela; Colacino, Evelina; Čelko, Ladislav (Frontiers in Chemistry, 2023)
There is still a need for synthetic approaches that are much faster, easier to scale up, more robust and efficient for generating gold(I)–thiolates that can be easily converted into gold–thiolate nanoclusters. Mechanochemical methods can offer significantly reduced reaction times, increased yields and straightforward recovery of the product, compared to the solution-based reactions. For the first time, a new simple, rapid and efficient mechanochemical redox method in a ball-mill was developed to produce the highly luminescent, pH-responsive Au(I)–glutathionate, [Au(SG)]n. The efficient productivity of the mechanochemical redox reaction afforded orange luminescent [Au(SG)]n in isolable amounts (mg scale), usually not achieved by more conventional methods in solution. Then, ultrasmall oligomeric Au10–12(SG)10–12 nanoclusters were prepared by pH-triggered dissociation of [Au(SG)]n. The pH-stimulated dissociation of the Au(I)–glutathionate complex provides a time-efficient synthesis of oligomeric Au10–12(SG)10–12 nanoclusters, it avoids high-temperature heating or the addition of harmful reducing agent (e.g., carbon monoxide). Therefore, we present herein a new and eco-friendly methodology to access oligomeric glutathione-based gold nanoclusters, already finding applications in biomedical field as efficient radiosensitizers in cancer radiotherapy.